The Impact of Leverage Buy-Out (LBO) Operations on Value Creation in Target Companies: An Empirical Study of the French Market - MEHREZ, Afef; FAKHFAKH, Hamadi (Revue du contrôle, de la comptabilité et de l’audit, 2026)
In an economic context shaped by the rapid evolution of financial markets, Leverage Buy-Out (LBO) transactions have become a key strategic tool for corporate restructuring and ownership transfer. This study aims to examine the impact of LBO operations on the performance and value creation of target companies. Using a sample of 183 French firms acquired through LBOs between 2013 and 2023.We adopted a longitudinal study design over a five-year horizon (two years before the LBO, the year of the transaction, and two years after). we compare their financial performance to that of similar non-LBO firms. The analysis is based on three indicators: ROA, ROE, and EVA. The results indicate that despite some performance decline post-LBO, the LBO-backed firms tend to outperform their peers, especially in the industrial sector.